Exploring the Impact of Social Support and Work-Family Conflict on Female Employees’ Performance in Indonesian Private Companies - Asbari, Masduki; Novitasari, Dewiana (International Journal of Social and Management Studies, 2025)
This study aimed to measure the effect of work-family conflict and social support (supervisor, peer, and family support) on the work performance of the female employees of two private companies in Indonesia. Data collection was done by simple random sampling of 145 population of female employees. The returned and valid questionnaire results were 123 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that work-family conflict have a (negative) significant effect on work performance, peer support and supervisor support have a (positive) significant effect on work performance. Meanwhile, family support has not a significant effect on work performance. This new research proposed a model for building work performance among the private company employees in Indonesia through enhancing social support and manage work-family conflict.